2015
DOI: 10.1371/journal.pgen.1005667
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Salmonella enterica O-Antigen Chain Length: A Tradeoff between Virulence and Bacteriophage Resistance

Abstract: The Salmonella enterica opvAB operon is a horizontally-acquired locus that undergoes phase variation under Dam methylation control. The OpvA and OpvB proteins form intertwining ribbons in the inner membrane. Synthesis of OpvA and OpvB alters lipopolysaccharide O-antigen chain length and confers resistance to bacteriophages 9NA (Siphoviridae), Det7 (Myoviridae), and P22 (Podoviridae). These phages use the O-antigen as receptor. Because opvAB undergoes phase variation, S. enterica cultures contain subpopulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 68 publications
(108 reference statements)
4
99
0
Order By: Relevance
“…An analogous situation has also been observed in other bacteria. For example in Salmonella , where phase variation of O‐antigen chain length potentiates the bacterium to be either phage resistant or virulent (Cota et al, ). This study showed that the effect was epigenetically regulated, and therefore only transient.…”
Section: Discussionmentioning
confidence: 99%
“…An analogous situation has also been observed in other bacteria. For example in Salmonella , where phase variation of O‐antigen chain length potentiates the bacterium to be either phage resistant or virulent (Cota et al, ). This study showed that the effect was epigenetically regulated, and therefore only transient.…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria local methylation changes may correlate with altered virulence behaviour and may underlie cell cycle-control in pathogens, endosymbionts or other microbial systems. Methylation is known to influence virulence functions in γ-proteobacteria, often by imposing bistability from phase-variable virulence promoters in subpopulations via transcriptional regulators such as Lrp, Fur or OxyR [5, 9, 42, 48, 5155]. Phenotypic heterogeneity in antibiotic drug tolerance in vivo (a state known as persistence), which is acquired in a low fraction of bacterial cells, may also underlie epigenetic changes induced stochastically by methylation, either deterministically (during the cell cycle) or environmentally.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of Salmonella with a virulent phage kills the opvAB OFF subpopulation and selects the opvAB ON subpopulation, preadapting these bacteria to survive phage challenge in a reversible manner. 28 Next, Olivier Espeli (College de France, Paris, France) gave a talk dedicated to the adaptation of the adherentinvasive E. coli LF82 strain inside mature phagolysosomes. This strain has been isolated from a Crohn's disease patient and has the ability to invade epithelial cells and to proliferate within macrophages.…”
Section: Session 2: Regulatory Mechanisms Of Adaptation Of Intracellumentioning
confidence: 99%